1999
DOI: 10.1071/rd99007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre- and post-mating nutritional status on hepatic function, progesterone concentration, uterine protein secretion and embryo survival in Meishan pigs

Abstract: This experiment examined whether the pre- or the post-mating diet had greater impact on embryo survival in Meishan gilts. Gilts received either a maintenance (1.15 kg day(-1); n = 12) or a high (3.5 kg day(-1); n = 12) diet during the oestrous cycle preceding mating. After mating, half the animals in each group received either the maintenance or the high diet until slaughter on Day 12. Gilts fed the high pre-mating diet had more corpora lutea (22.7 v. 19.0, SED = 0.98; P<0.001), increased embryo survival (95.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
1
24
0
3
Order By: Relevance
“…Increased feed intake also improves oocyte quality and embryo survival in sows and gilts (Zak et al 1997, Ashworth et al 1999a, Ferguson et al 2003. In the present study, and in the study described by Ferguson et al (2003), where intake was increased, improved oocyte maturity was associated with increased LH pulse frequency.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Increased feed intake also improves oocyte quality and embryo survival in sows and gilts (Zak et al 1997, Ashworth et al 1999a, Ferguson et al 2003. In the present study, and in the study described by Ferguson et al (2003), where intake was increased, improved oocyte maturity was associated with increased LH pulse frequency.…”
Section: Discussionsupporting
confidence: 67%
“…Studies involving altered feed intake have consistently reported an inverse relationship between the plane of nutrition and circulating steroid concentrations in the pig (Dyck et al 1980, Ferguson et al 2003. This relationship is thought to be attributed to increased steroid metabolism arising from increases in hepatic size, hepatic mixed function oxidase activity and portal blood-flow in well-fed animals (Prime & Symonds 1993, Ashworth et al 1999a). In the case of the high fibre diet used in the present study, the reduced circulating oestradiol concentrations observed are more probably due to interruption of enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historicamente, diversos autores já confirmaram os efeitos do flushing nutricional pré-cobertura sobre algumas respostas reprodutivas em leitoas (Flowers et al, 1989;Ashworth et al, 1999;Ferguson et al, 2003). Dentro dos limites alcançados por esta revisão, todavia, não se teve conhecimento de outros modelos experimentais como o proposto neste trabalho, direcionado especificamente para avaliar os efeitos de diferentes fontes de energia sobre a eficiência reprodutiva em marrãs cíclicas e francamente anabólicas.…”
Section: Methodsunclassified
“…A nutrição específica de marrãs no período que antecede sua primeira cobrição ou inseminação já é prática consolidada em boa parte da indústria suinícola, uma vez que diversos autores já demonstraram que altos níveis de energia nessa fase estão relacionados à melhoria do desempenho reprodutivo (Rhodes, 1991;Murgas, 1994;Ashworth et al, 1999;Ferguson et al, 2003;Brustolini et al, 2004). Essa prática é mundialmente conhecida como flushing nutricional.…”
Section: Introductionunclassified